Malaysia’s security offences bill : a good replacement of ISA? - Su, Hao’En (2012)
The newly introduced Security Offences Bill in Malaysia is meant to fill the gap left by the repeal of the Internal Security Act 1960 in tackling religious extremism. It is also an important tool for combating terrorism in Malaysia.